Pity as an effect of a passionate meaning in "The little match girl" by Andersen - Charnay, Thierry (Ondina - Ondine, 2021)
The matter is to study the pathemic dimension of the discourse (written and iconic) through of the expression of the passionate effect-sense of pity by comparing different recent versions for young people of Andersen's tale in the form of an album. By turns we will study : the structure of the passionate syntagmatic trial "pity", the pathemic role of "pity", the pathemic role of "self-pity" as well as the iconic expressions of the effect of the sense of pity.Keywords : pity, cruelty, effect-sense, passion, pathemic roles, icon, semantic